2014
DOI: 10.1111/pre.12054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen stress on Isochrysis galbana strain U4, a candidate for biodiesel production

Abstract: Lipid accumulation has been investigated in numerous microalgal species to assess their potential with respect to biodiesel production. The present work determines the effect of nitrogen stress on physiological and ultrastructural changes in Isochrysis galbana U4. This study is unique in showing the correlations between growth, lipid production, pigmentation and ultrastructural changes in Isochrysis cells undergoing nitrogen starvation. The continuation of algal growth after the complete depletion of external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…2). However, Roopnarain et al 41 corroborated our observation with similar findings from their investigation and further suggested that the microalgal strains relied on an internal nitrogen source from their cells for a few extra days after culture nutrient stripping. Having reviewed other literature that confirms the assertions of both Ansari et al 36 and Roopnarain et al, 41 we can conclude that the ability of microalgal cells to draw on internal nitrogen is a survival trait that is strain specific, among other factors.…”
Section: Growth Kinetics Nutrient Removal and Co 2 Sequestrationsupporting
confidence: 90%
“…2). However, Roopnarain et al 41 corroborated our observation with similar findings from their investigation and further suggested that the microalgal strains relied on an internal nitrogen source from their cells for a few extra days after culture nutrient stripping. Having reviewed other literature that confirms the assertions of both Ansari et al 36 and Roopnarain et al, 41 we can conclude that the ability of microalgal cells to draw on internal nitrogen is a survival trait that is strain specific, among other factors.…”
Section: Growth Kinetics Nutrient Removal and Co 2 Sequestrationsupporting
confidence: 90%
“…The LD synthesis in response to speci c cellular needs and their number per cell change according to the nutritional status conditions (Goold et al 2015). Also under N limitation or N depletion conditions, both the number and size of the LDs can increase and the chloroplast became imperceptible, because they act as a sink for membrane-derived fatty acids, including plastid membrane lipids that are degraded (Goold et al 2015;Roopnarain et al 2014;Siaut et al 2011).…”
Section: Cell Ultrastructurementioning
confidence: 99%
“…This observation could be due to the fact that the isolates' growth culture was stopped prior to significant nutrient stress being experienced by the algal cells. Even so, whilst the nitrate levels in the culture medium did decrease and became completely consumed by the end of the culture period as it was in the case of T. reginae; the isolate might still have been thriving on intracellular nitrogen reserves [54]. The measured dry wet biomass (DWB) and the optical cell densities at 750 nm of all monocultures also showed a linear regression association per Eqs.…”
Section: Biomass Productivity Growth Kinetics and Co 2 Biosequestration Ratesmentioning
confidence: 86%